2017
DOI: 10.1038/srep39994
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-dependent disruption of nucleo-cytoplasmic transport in ALS motor neurons

Abstract: Nuclear dysfunction in motor neurons has been hypothesized to be a principal cause of amyotrophic lateral sclerosis (ALS) pathogenesis. Here, we investigated the mechanism by which the nuclear pore complex (NPC) is disrupted in dying motor neurons in a mechanistic ALS mouse model (adenosine deaminase acting on RNA 2 (ADAR2) conditional knockout (AR2) mice) and in ALS patients. We showed that nucleoporins (Nups) that constituted the NPC were cleaved by activated calpain via a Ca2+-permeable AMPA receptor-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…5i, j ). These data suggest that the defects in the nucleocytoplasmic transport pathway are consistently observed in cortical neurons with ectopic expression of aggregated or mutant TDP-43, in fibroblasts and iPSC-derived neurons from ALS cases, as well as in a mechanistic ALS mouse model 26 . The dysregulation of nucleocytoplasmic shuttling and disruption of the NM and NPCs may be a common mechanism in both sALS and fALS exhibiting TDP-43 proteinopathy.…”
Section: Resultsmentioning
confidence: 66%
“…5i, j ). These data suggest that the defects in the nucleocytoplasmic transport pathway are consistently observed in cortical neurons with ectopic expression of aggregated or mutant TDP-43, in fibroblasts and iPSC-derived neurons from ALS cases, as well as in a mechanistic ALS mouse model 26 . The dysregulation of nucleocytoplasmic shuttling and disruption of the NM and NPCs may be a common mechanism in both sALS and fALS exhibiting TDP-43 proteinopathy.…”
Section: Resultsmentioning
confidence: 66%
“…The downstream calcium-dependent proteolytic enzymes known as calpains would then be activated (Adamec et al, 1998;Andres et al, 2013) and ultimately cleave substrates of receptors, enzymes or cytoskeletal proteins (Chan and Mattson, 1999), and possibly Nup358. In support of this notion, previous reports have shown that in diverse excitotoxic events, nucleoporins such as Nup153, Nup62, Nup88 and Nup358 were cleaved by activated calpains (Bano et al, 2010;Sugiyama et al, 2017;Yamashita et al, 2017). Moreover, under conditions of an increased calcium concentration, calpains contribute to the proteolysis of such AIS proteins as AnkG (Leterrier et al, 2015).…”
Section: Kcl Treatment Decreases Nup358 Expressionmentioning
confidence: 60%
“…Disruption of nucleoporins has been reported in an sALS mouse model (ADAR2 flox/flox /VAChT-Cre or AR2 mice),9 in which the adenosine deaminase acting on RNA 2 (ADAR2) was conditionally knocked out 10. Analogous changes in nucleoporins have also been observed in preliminary studies of the ADAR2-deficient motor neurons of sALS patients 10.…”
Section: Introductionmentioning
confidence: 77%
“…This study found that disruption of the NPC was correlated with TDP-43 mislocalization in the spinal motor neurons of patients with sALS. TDP-43 pathology occurs in motor neurons that demonstrate abnormal activation of calpains, and so we suspect that disruption of the NPC in sALS is related to calpain activation 10. NUP62 immunoreactivity was observed along the round-shaped nuclear membrane in normal motor neurons (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation